Intersecting journeys: the anthropology of pilgrimage and tourism - Badone, Ellen; Roseman, Sharon R. (University of Illinois Press, 2004)
"Starting from the premise that religion - broadly defined - involves a quest for meaning, Intersecting Journeys seeks to bridge the conceptual dichotomy between pilgrimage as religious travel and tourism as secular journeying." "The appeal of sacred sites remains undiminished at the start of the twenty-first century, as unprecedented numbers of visitors travel to Lourdes, Rome, Jerusalem, and Santiago de Compostela. This book's ethnographic analysis of the conflicts over resources and meanings associated with such sites, as well as the sense of community they inspire, provides compelling evidence emphasizing the links between pilgrimage and tourism." "As the papers in this interdisciplinary collection demonstrate, studies of these forms of journeying stand at the forefront of postmodern debates about movement and centers, global flows, social identities, and the negotiation of meanings."--Jacket